Distillation Equipment Design of Nutmeg Oil using Hybrid System. Issue 1 (February 2021) - Fitriadi, Nuzuli; Balkhaya; Saputra, Edi; Othman, S.
Abstract: The quality of nutmeg oil is determined by the quality of the nutmeg and the technology that are used in the purification process of the nutmeg. For instance, the distillation process will affect the yield and the essential quality of the production of the nutmeg oil are involving the boiler material, cooling system, and boiler design. The existing nutmeg oil distillation system is time consuming because the operators are highly depending on the firewood and the operators who must monitor closely throughout the time during the nutmeg oil refining process. The new distillation process and technique is based on the new type of boiler that is made from Stainless steel 304 with a diameter of 70 cm, length 120 cm, and with the thickness of 3 mm. The Boiler also comes with a new control system to precisely control the pressure and temperature. Meanwhile, the excess pressure of the boiler is controlled by pressure safety valve because the boiler is designed to withstand up to 3 bar maximum pressure capacity. The kettle is made of 304 Stainless steel equipped with a multi-storey basket to polish and to enhance the circulation and vapour pressure inside the boiler. The condenser pipes are made from the aluminium pipe to maximise the condensation process of the raw nutmeg oil. For the new distillation process, the hybrid system is utilised, where the sources of firewood and electricity are used as the source of energy to operate the boiler. It can be seen that hybrid kettle design reaches 2.8 tons with a 30% operating-saving cost. On top of that distillation time can be shortened to 48 hours from the previous 72 hours. It is stated that this hybrid boiler system is much more effective when compared to conventional systems. Laboratory test results stated that the distilled nutmeg oil has fulfilled the Indonesian national standard.